2018
DOI: 10.1097/md.0000000000012094
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of a modified American Joint Committee on Cancer staging scheme for resectable pancreatic ductal adenocarcinoma with a lymph node ratio-based N classification

Abstract: The recently launched 8th edition of the American Joint Committee on Cancer (AJCC) staging scheme for pancreatic ductal adenocarcinoma (PDAC) did not account for the impact of the total examined lymph node count on prognostic accuracy. In this population-based cohort study, we proposed a modified AJCC staging scheme by incorporating a lymph node ratio (LNR)-based N classification for patients with resectable PDAC.We analyzed 8615 patients with resectable PDAC from the Surveillance, Epidemiology, and End Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Nodal status and quantity are important, and nodal (N) staging is classified based on the number of metastatic lymph nodes, as N0 (0), N1 (1-3), and N2 (≥ 4), in the 8th edition of the American Joint Committee on Cancer [9]. Several other aspects of lymph node metastasis, including the lymph node ratio, are strong prognostic indicators [10]. A minimum of 12 lymph nodes should be examined to properly evaluate the N0 category [11,12].…”
mentioning
confidence: 99%
“…Nodal status and quantity are important, and nodal (N) staging is classified based on the number of metastatic lymph nodes, as N0 (0), N1 (1-3), and N2 (≥ 4), in the 8th edition of the American Joint Committee on Cancer [9]. Several other aspects of lymph node metastasis, including the lymph node ratio, are strong prognostic indicators [10]. A minimum of 12 lymph nodes should be examined to properly evaluate the N0 category [11,12].…”
mentioning
confidence: 99%
“… 20 26 Furthermore, a subdivision of N stage based on metastatic lymph node ratio (LNR), accounting for the total number of examined lymph nodes, was suggested for a more accurate prediction of survival. 24 , 27 …”
mentioning
confidence: 99%
“…The TNM staging system is a globally recognized standard for classifying the extent of spread of cancer and is widely accepted for predicting the prognosis and guiding treatment options for PDAC. The N classification of the 8th Edition of the American Joint Committee on Cancer (AJCC) scheme for PDAC, particularly recently proposed LNR (lymph node ratio)-based N classification for respectable PDAC, has been shown to more accurately predict patient response [27][28][29]. Therefore, we employed a multivariate Cox analysis to compare the predicting power of our signature with this clinical system.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, by using multivariate Cox analyses, we found that the path:00982_1 signature was an independent predictive factor as examined in all the available datasets, which included clinical information of age, gender, ethnicity, lymph nodes, grade, maximum tumor dimension, TNM (tumor, lymph nodes & metastasis) stages, N classification, molecular subtype (classical and basal) and history of diabetes [27][28][29] (Analytical data File 4).…”
Section: Identification Of the Path:00982_1 Subpathway Signaturementioning
confidence: 99%